Penggunaan Lagu “I See the Light” untuk Memperkaya Kosakata Bahasa Inggris di MTS Terpadu Berkah Palangka Raya dalam Program Pengabdian Masyarakat - Siti Anisah; Hesty Widiastuty; Misda Amallia Tuah Aji (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this community service activity is to enhance the English vocabulary mastery of students in class IX.A at MTs Terpadu Berkah Palangka Raya through the implementation of the